1992
DOI: 10.1105/tpc.4.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and Meiotic Chromosomal Recombination between Inverted Duplications in Transgenic Tobacco Plants.

Abstract: Homologous recombination has been extensively studied in bacteria, yeast, and more recently in animal cells, but little is known about this process in plants. We present here an analysis of meiotic and somatic chromosomal recombination between closely linked inverted duplications located on a single chromosomal region in tobacco. Transgenic tobacco lines were constructed by Agrobacterium transformation with plasmid vectors containing a functional hygromycin phosphotransferase (hyg) selectable marker flanked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Similar to homologous recombination between single-copy sequences, unequal interhomolog and interchromatid recombination between duplicated sequences ( Figure 2) has been observed in yeast (JACKSON and FINK 1981;JACKSON and FINK 1985;KLEIN 1984;KLEIN and PETES 1981;MOTOVALI-BASHI et al 2004;SZOSTAK and Wu 1980;THOMPSON and STAHL 1999), tobacco (TOVAR and LICHTENSTEIN 1992) and Arabidopsis (ASSAAD and SIGNER 1992;JELESKO et al 1999;MOLINIER et al 2004;OPPERMAN et al 2004). Also similar to equal recombination, unequal interchromatid recombination predominated during mitosis in a study conducted in yeast (JACKSON and FINK 1981), whereas unequal interhomolog recombination was preferred in meiosis (JACKSON and FINK 1985).…”
Section: Meiotic Recombination Among Tandemly Arrayed Duplicate Genesmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar to homologous recombination between single-copy sequences, unequal interhomolog and interchromatid recombination between duplicated sequences ( Figure 2) has been observed in yeast (JACKSON and FINK 1981;JACKSON and FINK 1985;KLEIN 1984;KLEIN and PETES 1981;MOTOVALI-BASHI et al 2004;SZOSTAK and Wu 1980;THOMPSON and STAHL 1999), tobacco (TOVAR and LICHTENSTEIN 1992) and Arabidopsis (ASSAAD and SIGNER 1992;JELESKO et al 1999;MOLINIER et al 2004;OPPERMAN et al 2004). Also similar to equal recombination, unequal interchromatid recombination predominated during mitosis in a study conducted in yeast (JACKSON and FINK 1981), whereas unequal interhomolog recombination was preferred in meiosis (JACKSON and FINK 1985).…”
Section: Meiotic Recombination Among Tandemly Arrayed Duplicate Genesmentioning
confidence: 99%
“…Although several studies in plants (ASSAAD and SIGNER 1992;MOLINIER et al 2004;TOVAR and LICHTENSTEIN 1992) have identified the mechanism by which unequal recombinants were generated (e.g., gene conversion, interchromosomal or intrachromosomal unequal recombination), the recombination breakpoints associated with unequal recombination events have been analyzed in only two related studies. Unequal recombination breakpoints (n=25) were distributed non-randomly in recombinants isolated from hemizygotes (i.e., unequal recombination between sister chromatids) in a synthetic tandemly arrayed cluster of RBCSB genes JELESKO et al 1999).…”
Section: Region-specific Trans-acting Modifiers Have Been Characterizmentioning
confidence: 99%
See 3 more Smart Citations